ARTISTRY, CULTURAL MEDIATION, AND THE GLOBAL PROMOTION OF BALINESE ARTS: THE CASE OF I NYOMAN WENTEN (Pena Cendekia Insani, 2026)
This study examines the role of I Nyoman Wenten in the development and promotion of Balinese arts in the United States. Using a qualitative descriptive-analytical approach, the study draws on interviews, observations, documentation, and literature sources to analyze Wenten’s artistic trajectory and cultural activities. The findings show that his artistry was shaped by Balinese cultural traditions, family influence, and formal artistic education. As an artist, educator, innovator, and cultural mediator, Wenten has contributed to the global dissemination of Balinese arts through performances, workshops, cross-cultural collaborations, and arts education in academic and community settings. He also adapted traditional performances to non-Balinese audiences while maintaining essential cultural values. This study concludes that Wenten plays a significant role in sustaining and promoting Balinese arts internationally by bridging traditional artistic practices with transnational cultural exchange.